2018
DOI: 10.18805/lr-4006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and character association studies for seed yield and component characters in soybean [Glycine max (L.) Merrill] under North-western Himalayas

Abstract: The present investigation was undertaken to assess the genetic variability and character associations for seed yield and component characters in 307 soybean germplasm lines. The lines were raised in augmented block design in four blocks during kharif 2014. Out of these, twenty seven promising genotypes were selected and forwarded for evaluation along with four checks in randomized block design with three replications at CSKHPKV, Palampur (H.P) during kharif 2015. The analysis of variance revealed the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Same finding were observed by Copur et al (2009) and Tayyar (2007). Haliloglu et al (2007) and Kumar et al (2019) also reported that seed yield showed positive correlation with days of flowering, plant height and number of grains per plant. The means comparison of genotypes, environment and their interaction is represented in Table 5, after combined analysis.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Same finding were observed by Copur et al (2009) and Tayyar (2007). Haliloglu et al (2007) and Kumar et al (2019) also reported that seed yield showed positive correlation with days of flowering, plant height and number of grains per plant. The means comparison of genotypes, environment and their interaction is represented in Table 5, after combined analysis.…”
Section: Resultsmentioning
confidence: 92%
“…Similar result were found by Miladinovic et al (2006) varieties vary in their growing days, longer this duration higher will be the yield and vice versa. Arshad et al, (2006) and Kumar et al (2019) also reported significant correlation of grain yield with days to maturity, number of branches per plant and 100-seed weight. The highest number pods per plant in the years' means i.e.…”
Section: Resultsmentioning
confidence: 94%
“…(2016) for the number of seeds per plant. Machado et al (2017) for the number of pods per plant, Sileshi et al (2019) for 100 seed weight and harvest index, Mehra et al (2020) and Kumar et al (2020) for biological yield per plant and harvest index.…”
Section: Resultsmentioning
confidence: 99%
“…The seed size illustrated by the weight of 100 seeds is an important factor in efforts to increase soybean production (Johnson et al 2001). Seed size has been known to be genetically inherited (Brian et al 2002;Kumar et al 2020) and has a positive direct effect on soybean yield (El-Badway and Mehasen, 2012).…”
Section: Diversity In Shape and Size Of Soybean Seedsmentioning
confidence: 99%